2020
DOI: 10.4103/joc.joc_5_20
|View full text |Cite
|
Sign up to set email alerts
|

Is subdivision of Atypia of Undetermined Significance AUS/Follicular lesion of undetermined significance cases according to detailed nuclear features vital for assessing the risk of malignancy?

Abstract: Background: It has been known that the “atypia of undetermined significance (AUS)/follicular lesion of undetermined significance (FLUS)” category is the most problematic category in Bethesda system due to its highly heterogeneous morphological features. Recently, it has been reported that aspirates including nuclear atypia in the AUS/FLUS category have a higher risk of malignancy. Aims: This study aimed to assess each nuclear property in aspirates with cytological atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…AUS-A subcategory and AUS-A2 subgroup significantly indicated BNs on histological examination. Considering the relationship of three-dimensional groups with high ROM, which is emphasized in some previous studies [ 31 , 32 ] and in the current study, perhaps architectural atypia, as well as nuclear atypia, may be nature-defining. So, detailed definition of architectural features as well as nuclear scoring and raising awareness in terms of three-dimensional groups may be useful in the correct evaluation of thyroid cytology.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…AUS-A subcategory and AUS-A2 subgroup significantly indicated BNs on histological examination. Considering the relationship of three-dimensional groups with high ROM, which is emphasized in some previous studies [ 31 , 32 ] and in the current study, perhaps architectural atypia, as well as nuclear atypia, may be nature-defining. So, detailed definition of architectural features as well as nuclear scoring and raising awareness in terms of three-dimensional groups may be useful in the correct evaluation of thyroid cytology.…”
Section: Discussionsupporting
confidence: 53%
“…The NS2 was significantly more common in FNAs of BNs. Guleria et al [ 31 ] and Kaymaz et al [ 32 ] used similar nuclear scoring models as in the current study and showed that the NS2-3 group was more frequently associated with malignancy. However, in these studies, ROM of NSs were not presented separately, and their focal/diffuse status was not evaluated.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Kaymaz et al. ( 24 ) reviewed the pathologic results of 209 AUS/FLUS nodules and found that the overall rate of malignancy was 27.8%, which decreased to 26.4% if only the nodules with nuclear atypia were assessed. This suggests that all nuclear properties are not equally effective in predicting the malignancy risk.…”
Section: Discussionmentioning
confidence: 99%